Mutations in desmoglein 1 cause diverse inherited palmoplantar keratoderma phenotypes: implications for genetic screening. (1st May 2017) - Lovgren, M.‐L.; McAleer, M.A.; Irvine, A.D.; Wilson, N.J.; Tavadia, S.; Schwartz, M.E.; Cole, C.; Sandilands, A.; Smith, F.J.D.; Zamiri, M.
Summary: The inherited palmoplantar keratodermas (PPKs) are a heterogeneous group of genodermatoses, characterized by thickening of the epidermis of the palms and soles. No classification system satisfactorily unites clinical presentation, pathology and molecular pathogenesis. There are four patterns of hyperkeratosis – striate, focal, diffuse and punctate. Mutations in the desmoglein 1 gene ( DSG1 ), a transmembrane glycoprotein, have been reported primarily in striate, but also in focal and diffuse PPKs. We report seven unrelated pedigrees with dominantly inherited PPK owing to mutations in the DSG1 gene, with marked phenotypic variation. Genomic DNA from each family was isolated, and individual exons amplified by polymerase chain reaction. Sanger sequencing was employed to identify mutations. Mutation analysis identified novel mutations in five families (p.Tyr126Hisfs*2, p.Ser521Tyrfs*2, p.Trp3*, p.Asp591Phefs*9 and p.Met249Ilefs*6) with striate palmar involvement and varying focal or diffuse plantar disease, and the recurrent mutation c.76C>T, p.Arg26*, in two families with variable PPK patterns. We report one recurrent and five novel DSG1 mutations, causing varying patterns of PPK, highlighting the clinical heterogeneity arising from mutations in this gene.